Long-Lasting Transcriptional Changes in Circulating Monocytes of Acute Q Fever Patients. (26th June 2019) - Raijmakers, Ruud Ph; Stenos, John; Keijmel, Stephan P; Ter Horst, Rob; Novakovic, Boris; Nguyen, Chelsea; Van Der Meer, Jos Wm; Netea, Mihai G; Bleeker-Rovers, Chantal P; Joosten, Leo Ab; Graves, Stephen R
Abstract: Objective: Although most patients recover from acute Q fever, around 20% develop Q fever fatigue syndrome (QFS), a debilitating fatigue syndrome that lasts at least 6 months. This study investigated transcriptional profiles of circulating monocytes and circulating cytokines as a subsequent mirror of myeloid cell function, 1 and 6 months after an acute Q fever infection. Methods: Total RNA of circulating monocytes was collected from 11 acute Q fever patients and 15 healthy controls, matched for age (±5 years) and sex. Samples were collected at a median of 27 days (baseline, interquartile range, 15–35 days) after the infection and again 6 months thereafter. Transcriptome analysis was performed using RNA sequencing. Additionally, concentrations of circulating interleukin (IL)-10, IL-1β, IL-1Ra, and IL-6 were measured in serum. Results: At baseline, acute Q fever patients clearly show a differential transcriptional program compared with healthy controls. This is still the case at follow-up, albeit to a lesser extent. At baseline, a significant difference in levels of circulating IL-10 ( P = .0019), IL-1β ( P = .0067), IL-1Ra ( P = .0008), and IL-6 ( P = .0003) was seen. At follow-up, this difference had decreased for IL-10 ( P = .0136) and IL-1Ra ( P = .0017) and had become nonsignificant for IL-1β ( P = .1139) and IL-6 ( P = .2792). Conclusions: We show that an acute Q fever infection has a long-term effect on the transcriptional program of circulating monocytes and, therefore, likely their myeloid progenitor cells, as well as concentrations of circulating IL-10, IL-1β, IL-1Ra, and IL-6. Abstract : This study shows that an acute Q fever infection has a long-lasting effect on the transcriptional program of circulating monocytes and, therefore, likely their myeloid progenitor cells as well as concentrations of circulating interleukin (IL)-10, IL-1β, IL-1Ra, and IL-6.